Commonality and Particularity in Ethics
X, 493 p.
Keywords: Original essays by distinguished philosophers from different fields of philosophy are brought together in this book. Reflections on moral discourse and its contexts are provided and the authors discuss the nature and tasks of moral philosophy. The overall collection creates a dialogue between different philosophical views.